Women's discovery of meaning and their HIV test results - Olney, Adrienne (Kansas State University, 2008)
The risk of HIV infection continues to be high in the United States, with women being one of the most vulnerable populations. Medical tests to determine an HIV-positive diagnosis and to subsequently chart the progression of the disease and the effectiveness of the medications are central to the lives of these women. This paper will focus on how women find meaning in these test results and how these meanings affect the way they view their lives and their relationships. Women are also often in particularly vulnerable positions, and this paper will discuss how they deal with this disproportionate lack of power both before and after HIV infection. It is important to therapists working with these women to have an understanding of how women make meaning of both their HIV test results and power differentials. The implications for therapy include helping the client and her family members understand this new situation and the meanings it has for their lives and relationships.
Keywords: HIV/AIDS; Women; Psychology, General (0621)